A Perturbative Method for Calculating the Impedance of Coils on Laminated Ferromagnetic Cores. (26th September 2010) - Maximov, Serguei; Castillo, Allen A.; Venegas, Vicente; Guardado, José L.; Melgoza, Enrique
Abstract : A new set of formulas for calculating the self and mutual impedances of coils on straight and closed laminated ferromagnetic cores of circular cross-section has been derived. The obtained formulas generalize the well-known formulas for impedances of coils on homogeneous ferromagnetic cores, for the case of laminated cores, and improve the previously known formulas for laminated cores. The obtained formulas are fully consistent with Maxwell's equations and, therefore, offer an excellent accuracy. The perturbation theory and the average field technique are used to solve Maxwell's equations inside and outside the core. The solution inside the core can also be used in the analysis of thermal effects occurring inside the laminated core.